CORRELATION OF THE DEFINITION OF “PUBLIC CONTROL” OF REPRESENTATIVE AUTHORITIES IN DOMESTIC SCIENTIFIC APPROACHES - Matvieienko , I.; Kuleshov , V. (Theory and Practice of Public Administration, 2020)
The article analyzes and correlates the definition of “public control” of representative authorities within domestic scientific approaches. It is revealed that there is no common understanding of the categories “public control” and “public control of representative authorities”. The latter is studied in certain areas of public life or public administration, which leads to the development of separate methodological approaches to the organization of this control in accordance with the scientific fields in which the researches are conducted. The analysis demonstrates the existence of a wide range of interpretations of public control in the context of subject-object relations of governmental authorities and local self-government, in particular: forms; mechanisms; impacts; activities; interaction; relationships; feedback; activity of citizens; control systems; functions; ways; methods; tools; rights; processes. Domestic views on the understanding of the meaning of public control are generalized, which demonstrates a wide range of interpretations in the context of relations between governmental authorities and local self-government. The types of public control used in domestic scientific works are distinguished. Public control is mostly studied in the areas of local self-government, public administration, local budget, finance, education, law enforcement and fiscal authorities. A small number of scholars point out the differences between public control in governmental authorities and local self-government. There is also a difference between control exercised by the authorities and society. It is revealed that there is no single categorical apparatus. That does not allow to develop a single methodological approach to the forms, methods, techniques and tools of effective public control at the local level.